Identity in Zadie Smith's White Teeth - Sajbtová, Kateřina (Univerzita Pardubice, 2007)
The bachelor work focuses on the question of maintaining a religious identity in a multicultural society, namely today's Britain. Using Zadie Smith's novel White Teeth, it explores the conflicts that can arise during the coexistence of both eastern and western culture. It also looks at the differences between the first and second generation family members portrayed in the novel. Particular attention is also paid to the religious identity of the ethnic and minority groups living in British society. The work also analyzes the changes in one's own perception of self identity whilst living in and experiencing the effects of British culture.
Identita v díle Zadie Smith Bílé Zuby
Keywords: religious identity; multicultural society; minority groups; conflicts; náboženská identita; multikulturní společnost; menšinové skupiny; konflikty